2015
DOI: 10.1002/chem.201501499
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Homopolar Dihydrogen Bonding CH⋅⋅⋅HC on Coordination Geometry: Experimental and Theoretical Studies

Abstract: The reaction of the N-thiophosphorylated thiourea (HOCH2 )(Me)2 CNHC(S)NHP(S)(OiPr)2 (HL), deprotonated by the thiophosphorylamide group, with NiCl2 leads to green needles of the pseudotetrahedral complex [Ni(L-1,5-S,S')2 ]⋅0.5 (n-C6 H14 ) or pale green blocks of the trans square-planar complex trans-[Ni(L-1,5-S,S')2 ]. The former complex is stabilized by homopolar dihydrogen C-H⋅⋅⋅H-C interactions formed by n-hexane solvent molecules with the [Ni(L-1,5-S,S')2 ] unit. Furthermore, the dispersion-dominated C-H⋅… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 88 publications
6
27
0
Order By: Relevance
“…for the C−F⋅⋅⋅F−C interaction, which was responsible for the integrity of a self‐assembled 2D supramolecular architecture using fully fluorinated compounds . The Δ E values of comparable magnitude have been reported for other non‐covalent interactions …”
Section: Resultssupporting
confidence: 58%
“…for the C−F⋅⋅⋅F−C interaction, which was responsible for the integrity of a self‐assembled 2D supramolecular architecture using fully fluorinated compounds . The Δ E values of comparable magnitude have been reported for other non‐covalent interactions …”
Section: Resultssupporting
confidence: 58%
“…Further Valence Bond studies have revealed [78], in line with our conclusions, that, apart from the crucial dispersion term, also the σ/σ*(C-H) polarization/charge transfer and electrostatic contributions are important. Recently, numerous reports are present in the literature on the stabilizing nature of CH¨¨¨HC interactions in various types of hydrocarbons [37,38,[79][80][81][82][83][84][85], as well as their importance in catalysis [42,43,86].…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that these types of connections are intuitively considered as destabilizing due to the lack of electrostatic attraction between hydrogen atoms-homopolar dihydrogen interactions (especially the intramolecular ones) are still a matter of debate in the literature [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]. Very recently more and more evidence has been reported in the literature that highlight the stabilizing nature of homopolar dihydrogen interactions [17,21,29,[36][37][38][39][40][41][42][43][44][45][46]. Accordingly, in this work we provide complementary results which shed light on energetic, quantitative and qualitative characteristics of non-covalent interactions that contribute to the stability of LiN(CH3)2BH3 and KN(CH3)2BH3 crystals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Firouzi and Shahbazian explored theoretically the existence of very short CH···HC intramolecular contacts . The additive character of theses interactions has been observed, for instance, in the spatial arrangement of “molecular ladders.” In another interesting work, the stabilization of a pseudotetrahedral Ni II complex was achieved via attractive CH···HC interactions . Recently, the importance of CH···HC contacts in the crystalline phases of several hydrogen storage materials has been pointed out …”
Section: Introductionmentioning
confidence: 99%